Recommendations for screening, monitoring, prevention, prophylaxis and therapy of hepatitis B virus reactivation in patients with haematologic malignancies and patients who underwent haematologic stem cell transplantation—a position paper. (December 2017) - Sarmati, L.; Andreoni, M.; Antonelli, G.; Arcese, W.; Bruno, R.; Coppola, N.; Gaeta, G.B.; Galli, M.; Girmenia, C.; Mikulska, M.; Pane, F.; Perno, C.F.; et al.
Abstract: Scope: Hepatitis B virus (HBV) infection reactivation is associated with high morbidity and mortality in patients with haematologic malignancy and/or haematopoietic stem cell transplantation (HSCT). However, information on this issue is limited. The scope of this position paper is to provide recommendations on HBV screening, monitoring, prophylaxis, treatment and vaccination in the patients described above. Methods: These recommendations were developed from one meeting of experts attended by different Italian scientific societies as well as from a systematic literature review (of articles published through December 31, 2016) on HBV infection in haematologic patients and in patients who underwent haematopoietic stem cell transplantation published in the same issue of the journal. The Grading of Recommendations Assessment, Development and Evaluation (GRADE) methodology was used to assess each recommendation's quality. Questions addressed: These recommendations provide the answers to the following questions: (a) HBV screening and monitoring: Who should be screened before chemotherapy? Which screening tests should be used? Should HBV-DNA detection be used to monitor HBV reactivation before starting antivirals? What is the best timeline to monitor HBV reactivation? (b) Prophylaxis in HBsAg-positive patients: Which antiviral drugs should be used to treat HBsAg-positive patients? How long should antiviral prophylaxis be provided to HBsAg-positive patients? (c) Prophylaxis in patients with resolved HBV infection: Which patients with resolved HBV infection should receive antiviral prophylaxis? Which antiviral drug should be used? How long should antiviral prophylaxis be provided? (d) HBV infection management strategy in autologous (auto-HSCT) and allogeneic HSCT (allo-HSCT): Which HSCT recipients should receive antiviral prophylaxis? Which antiviral drug should be used? How long should antiviral prophylaxis be provided? (e) Choice of antiviral drugs in the treatment of HBV reactivation: Should third-generation anti-HBV drugs be preferred to first- or second-generation antiviral drugs in the treatment of HBV reactivation with or without hepatitis flare in haematologic patients? (f) Immunization against HBV in patients with haematologic malignancies and/or patients who underwent HSCT: Should these patients be vaccinated? Which HBV vaccination schedule should be adopted? Recommendations: Haematologic patients should be screened for hepatitis B surface antigen (HBsAg) plus anti-hepatitis B core protein (HBc), and HBV DNA before chemotherapy. HBV DNA levels should be monitored monthly in all HBV-positive patients who do not receive prophylaxis. HBsAg-positive haematologic patients and those undergoing HSCT should receive third-generation antiviral therapy as prophylaxis. Anti-HBc-positive lymphoma patients and those receiving HSCT should receive antiviral prophylaxis. All HBV-negative haematologic patients should be vaccinated for HBV. The acquisition of data from well-designed studies is desirable in the near future.